HUBUNGAN ANTARA KEADILAN PROSEDURAL, JOB STRESS, KOMITMEN ORGANISASI DAN KEINGINAN BERPINDAH (Study pada Tenaga Akuntansi di Provinsi Riau dan Kabupaten Bengkalis) - Basri, Yesi Mutia (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
This study investigates relationship between of procedural fairness, job stress, organizationalcommitment and turnover intention accounting staff contracts in local government. Datawere collected through a questionnaire survey of 51 accounting staff contracted by theprovincial government of Riau and Bengkalis. Data analyzed by a structural equation modelwith Partial Least Square (PLS). The result showed procedural fairness was positivelyrelated to job stress and turnover intention, Job stress positively related to turnoverintention, and organizational commitment was negatifly related to turnover intention.Procedural fairness does not direct effect on turnover intention, but mediated organizationalcommitment. The result showed that job stress not relation to organizational commitment.Keywords: Procedural fairness, job stress, organizational commitment, turnover intention